Treating Children With Advanced Rheumatic Heart Disease in Sub-Saharan Africa: The NGO EMERGENCY's Project at the Salam Centre for Cardiac Surgery in Sudan - Miccio, Rossella; Quattrociocchi, Maria; Valgoi, Lorenzo; Chatenoud, Liliane; Lentini, Salvatore; Giovanella, Elena; Rolla, Luca; Erba, Nicoletta; Gatti, Sofia; Rocchi, Daniela; Saad, Manahel Badr; Salvati, Alessandro; et al. (Frontiers in Pediatrics, 2021)
Rheumatic heart disease is endemic in Sub-Saharan Africa and while efforts are under way to boost prophylaxis and early diagnosis, access to cardiac surgery is rarely affordable. In this article, we report on a humanitarian project by the NGO EMERGENCY, to build and run the Salam Centre for Cardiac Surgery in Sudan. This hospital is a center of excellence offering free-of-charge, high-quality treatment to patients needing open-heart surgery for advanced rheumatic and congenital heart disease. Since it opened in 2007, more than 8000 patients have undergone surgery there; most of them Sudanese, but approximately 20% were admitted from other countries, an example of inter-African cooperation. The program is not limited to surgical procedures. It guarantees long-term follow-up and anticoagulant treatment, where necessary. By way of example, we report clinical features and outcome data for the pediatric cohort: 1318 children under the age of 15, operated on for advanced rheumatic heart disease between 2007 and 2019. The overall five-year survival rate was 85.0% (95% CI 82.7-87.3). The outcomes for patients with mitral valves repaired and with mitral valves replaced are not statistically different. RHD in children is an indicator of poor socio-economic conditions and an inadequate health system, which clearly will not be cured by cardiac surgery alone. Nevertheless, the results achieved by EMERGENCY, with the crucial involvement and participation of the Sudanese government over the years, show that building a hospital, introducing free cardiac surgery, and offering long-term post-operative care may help spread belief in positive change in the future